Production of Bio Charcoal Briquettes Made from Coal and Palm Fronds - Sandi Asmara; Winda Rahmawati; Tamrin; Ipang Setiawan (Open Global Scientific Journal, 2023)
Biomass from oil palm fronds has not been effectively utilized in Central Lampung, there is a need for alternative processing of palm oil fronds into more useful materials. One method of processing palm fronds is to create bio charcoal briquettes, which are used as an alternative fuel. The purpose of this research was to see how palm fronds and particle size of palm oil fronds affected the properties of bio charcoal briquettes. The factorial completely randomized design (CRD) was used in the research with one factor, namely the particle size of the oil palm fronds passing through the sieve with one treatment, namely 20 mesh. To produce 25 experimental units, the study used five treatments with five replications. The obtained material was then tested for LSD. The results revealed that palm fronds had no impact on briquette density, moisture content, compressive strength, shatter resistance index, or rate of burning. The particle size of palm leaves going through the 20 mesh sieve affects density, compressive strength, shatter resistance index, and burning rate significantly. The findings revealed the following features of bio charcoal briquettes: The moisture content is 5.17-6.89%, the heating value is 4372.42 - 5074.50 cal/g a density of 0.568-0.674 g/cm3, a compressive strength of 3.85 - 4.58 kg/cm2, a shatter resistance index of 12.58-17.19%, a burning rate of 1.40-1.47 gram/minute, and a bottom temperature of 287°C. (for 60 minutes and a mass of 200 grams).